Antitumor and immunomodulatory effects of weikangfu granule compound in tumor-bearing mice - Nie, Xiaohua (Elsevier, 2006)
Background: Weikangfu granule compound (WKC) is a drug preparation based on a clinical prescription drug, Weikangfu-tang, which has been found to have therapeutic effects on gastric cancer. WKC comprises 7 components, including polysaccharides, saponin, flavonoids, and essential oil. Objective: The purpose of this study was to assess the antitumor and immunomodulatory effects of WKC in a tumor-bearing rodent model. Methods: Male and female Kuming mice weighing ∼20 g were subcutaneously implanted with sarcoma 180 (S180) tumor cells and randomly assigned to 1 of 5 treatment groups: oral WKC 175, 350, or 525 mg/kg·d, isotonic saline (negative control), or intraperitoneal cyclophosphamide 25 mg/kg·d (positive control). All treatments were administered daily for 10 days. After euthanization on day 11, the mice, tumors, and spleens were weighed. Lymphocyte proliferation and cytotoxic T lymphocyte (CTL) activity were determined using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide cellular viability assay method. Macrophage phagocytosis was identified using a yeast test. Results: Fifty mice were included in the study (10 mice were assigned to each group). The tumors of the mice administered WKC 175, 350, and 525 mg/kg·d were significantly regressed, as determined using MICs, compared with those in the negative-control group (P<0.05, P<0.01, and P<0.01, respectively), and the inhibitory rates were 30.43%, 46.72%, and 54.35%, respectively. Compared with those in the negative-control group, CTL activities and lymphocyte proliferations in the presence of concanavalin A were significantly greater in the WKC-treated groups at all doses (CTL activities: P<0.05, P<0.01, and P<0.01, respectively; lymphocyte proliferations: P<0.05, P<0.01, and P<0.01, respectively). In the groups receiving WKC 175, 350, and 525 mg/kg·d, the phagocytic rates were 1.5- to 2.0-fold those in the negative-control group (P<0.05, P<0.01, and P<0.01, respectively). In the groups receiving WKC 175, 350, and 525 mg/kg·d, the phagocytic indexes were 3.7- to 5.0-fold those in the negative-control group (all, P<0.01). In contrast, lymphocyte proliferation in the positive-control group was significantly less compared with that in the negative-control group (P<0.01), but no significant differences were found in CTL activities or macrophage phagocytosis between these 2 groups. Conclusion: The results of this study in a rodent model suggest that WKC exhibited antitumor and immunomodulatory activities in S180-bearing mice, and that WKC improved nonspecific and specific immune functions in mice, such as lymphocyte proliferation, CTL activity, and macrophage phagocytosis.